The association between obstructive sleep apnea syndrome and epilepsy: the prevalence and clinical predictors of sleepiness - Musa, Muhamad Yusri (2010)
Epilepsy and Obstructive Slee Apnea Syndrome (OSAS) are both associated with abnormal brain activity and frequently coexist. Epilepsy patients were found to be drowsier when compared with general population using the Epworth Sleepiness Scale. The aim is to study obstructive sleep apnea syndrome (OSAS) in epilepsy patients, as well as the prevalence of obstructive sleep apnea and the predictors of sleepiness among epileptics. This was a prospective cross sectional study in HUSM on patients already diagnosed and treated with epilepsy. The study was conducted from November 2008 to April2010. The consented participants who fulfilled the criterias were interviewed using questionnaire regarding demographic data, symptoms of obstructive sleep apnea and Epsworth Sleepiness Scale, followed by full ear, nose and throat examination and overnight polysomnography (PSG). Five of sixty participants (8.3%) were diagnosed with OSA and four of them were males. OSA was mild in one patient, moderate in two patients and severe in the other two. Age, neck circumference, ESS score and BMI were significantly associated with OSA (p value <0.05). Epilepsy-related risks (type of seizures, duration and type of AED) have no significant association with OSA. The prevalence ofOSA among epilepsy patients is 8.3%. The use of Malay version ofESS scale is appropriate and effective in screening patients for OSAS. Future role of PSG as part of assessment in high risks epileptics is recommended.